Pemaknaan Jihad Dan Problem Aplikasinya Dalam Tataran Sosial - Patompo Adnan (Universitas Islam Negeri Mataram, 2006)
The precise meaning of jihad is confusing to even moslem themselves and, let alone, nonmoslem. Many conceive jihad as a sort of physical war against enemies. Jihad also means conquering and subjugating nonmuslims and forcing them to convert to Islamic faith as their religion. But, if we look at in detail the Quranic verses and the hadith, we shall underline that jihad could also be meant as any kind of holding God’s commands. Observing religious practices, helping the poor, being patient and all good deeds are also jihad. Jihad in terms of the war is only allowed when muslims are being attacked by enemies, as what now happens in Afghanistan and Palestine. The association of jihad with violence, especially after the September 11 attack in the U.S. is a more political trick of the West, especially the U.S., rather than an exact definition of jihad itself.